Strategi Implementasi Literasi Visual untuk Meningkatkan Minat Baca Siswa Sekolah Dasar Kelas 4 - Firda Mawaddatul Jannah; Munawarotus Sholihah; Syailin Nichla Choirin Attalina (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Reading interest is an intrinsic motivation that encourages students to actively engage in reading activities with a sense of enjoyment and autonomy. This study was motivated by the low reading interest among fourth-grade elementary students, often caused by reading materials dominated by plain text without visual support. Visual literacy offers an innovative approach by utilizing media such as picture books, educational comics, infographics, and videos to attract attention and enhance students’ comprehension. This research aims to analyze the implementation strategy of visual literacy to improve reading interest among fourth-grade students. The method used is Classroom Action Research (CAR) based on the Kemmis and McTaggart model conducted in two cycles. The findings indicate that visual media fosters interactive and meaningful learning experiences, leading to a significant increase in students’ reading interest. These results are expected to contribute to strengthening a culture of literacy in elementary schools